Hemorrhagic cerebral venous infarction after vein injury during intraoperative lesion resection: incidence, hemorrhagic stages, risk factors and prognosis - Wu, Yingxi; Tian, Qilong; Wang, Shoujie; Li, Kailu; Feng, Dayun; Cai, Qing (Frontiers in Neurology, 2024)
Objective Cerebral venous infarction (CVI) after vein injury during intraoperative lesion resection is associated with intracranial hemorrhage. We conducted this study to identify the incidence, clinical and imaging features, and prognosis of hemorrhage CVI. Methods We performed a retrospective analysis of patients with confirmed CVI after vein injury who underwent craniotomy in our hospital. Postoperative clinical symptoms were observed, and imaging features were compared between patients with and without intracranial hemorrhages through CT examination. Variables were analyzed using univariate and multivariate regression analyses. Results Among 2,767 patients who underwent craniotomy, 93 cases of injured veins were identified intraoperatively. Hemorrhagic CVI was found in 38% (35/93). Multivariate analysis revealed that midline approach, meningioma, postoperative seizures, disorders of consciousness and interval in hours < 72 h were identified as predictors of hemorrhagic CVI. After 3 months of follow-up, the prognosis was poor in 15 cases (16%, 15/93), including death (two cases), vegetative survival (four cases), and severe disability (nine cases). Conclusions Hemorrhagic CVI, as a critical complication after venous injury, can have disastrous consequences. Do not injure known veins intraoperatively. In case of injury, requisite remedial measures should be adopted during and after surgery.